Human Trafficking Prevention and Combat Under Regulations of International Law and Practice in Vietnam - Thuong, Mac Thi Hoai (Journal of Law and Legal Reform, 2025)
The situation of human trafficking crime is becoming increasingly complicated, evidenced by an increasing trend in severity, number of cases, and the use of sophisticated methods and tricks. Human trafficking is identified by the United Nations as one of the four most dangerous crimes in the world, as outlined in the Global Crime Prevention Program 2013. It is conducted by organized, transnational criminal groups. Therefore, international cooperation in addressing it is an indispensable and objective requirement. Vietnam has been actively participating in international commitments to combat human trafficking prevention, such as International Convention on the Rights of the Child (1989), the Optional Protocol to the International Convention on the Rights of the Child, Trafficking in Children, Child Prostitution and Child Pornography (2000), United Nations Convention against Transnational Organized Crime (2000), the ASEAN Convention Against Trafficking in Persons, Especially Women and Children (ACTIP Convention), among others. By analyzing both international and Vietnamese laws on human trafficking prevention, combined with the practice of anti-trafficking efforts in Vietnam, this paper highlights that while current Vietnamese law has been promoting its positive effects, some limitations and shortcomings need to be addressed in order to comply with international law and meet practical requirements of anti-trafficking efforts. Thereby, the paper proposes some recommendations for improving Vietnamese law on human trafficking prevention to align with the requirements of international legal standards and the actual needs of human trafficking prevention in Vietnam.